KAJIAN PERUBAHAN UKURAN RONGGA ZEOLIT RHO BERDASARKAN VARIASI RASIO Si/Al DAN VARIASI KATION ALKALI MENGGUNAKAN METODE MEKANIKA MOLEKULER - Wahdana Kusuma Sari; Rahmat Gunawan; Erwin Erwin (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2016)
The structure modeling of zeolite RHO with variation of Si/Al ratio (5; 4.33; 3.8; 3.36; 3; 2.69; 2.43; 2.2; 2) and variation of alkaline cations (Li+, Na+, K+, Rb+, Cs+, Fr+) calculated by the molecular mechanics method has been investigated. The result shows that the structure of zeolite RHO with Si/Al ratio 3.36 has the most stable structure with a minimum energy 2652.0308 kcal/mol. The most stable structures of zeolite RHO impregnated with cation is that impregnated with Fr+ (alkaline) with a minimum energy 3006.6587 kcal/mol. The result shows that the zeolite RHO structure with cations Fr+ (alkaline) has the largest pore diameter which potentially has the best adsorption capacity.